Does heat cause homicides? A meta-analysis - Vojtěch Mišák (Charles University in Prague, Institute of Economic Studies (IES), 2023)
Several studies provide evidence that heat is positively associated with criminal activity. However, the empirical literature does not provide conclusive evidence about the effect of high temperature on homicides. I examine 156 estimates from 20 studies on the relationship between temperature and homicide rates. In particular, in this meta-analysis I study publication bias using linear and nonlinear techniques together with Bayesian model averaging to explain the heterogeneity in the estimates. After correcting estimates from the publication bias, I find no significant effect of temperature on homicide rates. Moreover, monthly data produce larger estimates. Conversely, studies using data from Asia or the OLS estimation method lead to smaller estimates.
Keywords: K10; K14; K32; Q54; 330; environmental law and economics; economic analysis of crime; meta-analysis; Bayesian model averaging; publication bias